Late Permian-Triassic magmatic evolution in the Jinshajiang orogenic belt, SW China and implications for orogenic processes following closure of the Paleo-Tethys - Zi, Jianwei; Cawood, P.; Fan, W.; Tohver, E.; Wang, Y.; McCuaig, T.; Peng, T. (American Journal of Science, 2013)
Growth of continental crust involves the complex interplay of subduction zone magmatism, to generate the crust, followed by stabilization through crustal thickening, magmatism and ultimately isolation from the active plate margin. The Jinshajiang orogenic belt, SW China, provides an exceptional record of continental development as the result of closure of the Paleo-Tethys seaway and ensuing collision. A compilation of U-Pb age and geochemical data for the plutonic and volcanic rocks within the southern part of the Jinshajiang orogenic belt, including new high-precision ages for the Ludian granitoid batholith of 231 to 220 Ma, enables us to explore the interaction between magmatism and orogeny in the context of the Paleo-Tethys closure and continental amalgamation. These age and geochemical constraints, in conjunction with other geologic evidence, suggest that subduction of the Paleo-Tethys ocean dominated local tectonics prior to the Triassic, creating a volcano–plutonic arc along the eastern margin of the Qamdo-Simao terrane. Following consumption of the ocean, collision zone magmatism, dated at 247 to 237 Ma, was manifested by eruption of voluminous volcanic rocks in a suture-parallel zone. Crustal anatexis was contemporaneous with the earliest phases of collision, producing high-silica rhyolites of Early Triassic age (ca. 247-246 Ma). Between 245 and 237 Ma, the local tectonic regime switched from compression to extension, probably due to strain partitioning caused by oblique convergence, which led to the development of rift-basins and extensive syn-tectonic bimodal volcanism associated with deep-water sediments. From 234 Ma to 214 Ma, the emplacement of high-K, calc-alkaline granodiorites-monzogranites occurred prior to, or during, isostatic uplift and extension, probably caused by breakoff of the subducted slab. The resultant exhumation brought deep-seated granitoid batholiths to the surface, and was contemporaneous with intrusion of ultramafic-mafic melts. Ophiolitic mélange (ca. 362-294 Ma) and collision-related magmatic suites (247-214 Ma) are unconformably overlain by a Late Triassic (229-217 Ma) conglomerate-rich sequence that represents an overlap assemblage, across the Qamdo-Simao terrane (Indochina) and Yangtze Block of South China.